Fear and cultural background drive sexual prejudice in France – a sentiment analysis approach - Fronhofer N.-M.; Herbert C.; Durand V.; Alvergne A.; Raymond M.; Barkat-Defradas M. (Open Psychology, 2022)
Sexual prejudice and its negative consequences remain major issues in Western societies, and numerous studies have tried to pinpoint its sociocultural underpinnings. However, most research has operationalized sexual prejudice via self-report measures or via implicit association tests (IATs), although it surfaces in language use and can be traced in spontaneous speech.